Pengaruh Pendekatan Matematika Realistik Terhadap Kemampuan Penyelesaian Soal Cerita Pada Mata Pelajaran Matematika di Kelas II MI Qubbatul Islam Karang Taliwang Tahun Pelajaran 2024/2025 - Zunnun, Lalu Mathlubi Ali; Wijaya, Triansyah Andra; Dewi, Desiani Sutra; Sriyati, Sriyati; Ruqoiyyah, Siti (PRIMER : Jurnal Ilmiah Multidisiplin, 2024)
This research is motivated by the low ability of students in solving the story problem. So to improve the ability of the material researchers use alternative learning by using a realistic mathematical approach. This realistic mathematical approach is oriented to the real thing. So as to facilitate students to understand the abstract concept. The purpose of this study is to determine the effect of realistic mathematical approach to the ability to solve the story problem addition, subtraction, and division. The research method used in this research is quantitative research method with pre-experimental research design with the form of One-Group Pretest-Posttest Design. This research was conducted in class III SDN 2 Setiamulya Kecamatan Tamansari Kota Tasikmalaya. The instrument used in this research is giving test. The test is performed before treatment (pretest) and after treatment (posttest). Data analysis is done by quantitative data analysis with the help of SPSS 16.0 and Microsoft Excel 2013 program. Based on the data analysis obtained from the research, it can be concluded that the process of learning mathematics with realistic mathematics approach in accordance with the four stages of realistic mathematical approach can improve students' abilities addition, subtraction, and division in grade II primary school. The increase in capability can be seen from the average of pretest and posttest results which increased from 6 to 12.